Implementasi Peraturan Daerah Provinsi DKI Jakarta Nomor 3 Tahun 2005 dalam Rangka Penguatan Nilai Tata Budaya Melalui Pembentukan Kelurahan di Kawasan Perkampungan Budaya Betawi - Ghiyats, Abdullah Jawwad; Firdausy, Adriana Grahani (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis study aims to determine the implementation of the Jakarta Provincial Regulation No. 3 of 2005 in order to strengthen the governance of cultural values through the establishment urban villages in the Betawi Cultural Village area and supporting factors as well as inhibiting factors for the formation of villages in the Betawi Cultural Village area. The research method used in this research is sociolegal research which is descriptive analytical in nature. This research approach uses a qualitative approach. Types and sources of legal materials used in this study include primary and secondary legal materials. The technique of collecting material through interviews and document studies. The analysis technique used is a qualitative analysis technique. Implementation of DKI Jakarta Provincial Regulation Number 3 of 2005 in the context of strengthening the value of cultural governance through the formation of sub-districts in the Betawi Cultural Village area can be demonstrated through the fulfillment of the requirements as stipulated in the Decree of the Governor of the Special Capital Region of Jakarta Province Number 3 of 2004 concerning Guidelines for Establishment and Expansion. , The Abolition and Merger of Administrative Regions / Districts, Districts and Villages in the Province of the Special Capital Region of Jakarta, namely: the availability of regional potential, the creation of conductive socio-cultural conditions, achieving anadequate population, and having an adequate area. Even so, there is one condition that has not been fulfilled, namely another possible consideration in the form of the absence of a sub-district office that will become the center of government. As for the specialty in this sub-district is the Betawi Cultural Village Area Management Unit which was formed to preserve Betawi culture. There are several factors supporting and inhibiting factors for the implementation of DKI Jakarta Provincial Regulation Number 3 of 2005 in the context of strengthening the value of cultural governance through the formation of sub-districts in the Betawi Cultural Village area. Supporting factors for the formation of sub-districts in the Betawi Cultural Village Area, namely: support from Betawi cultural observers related to the need for their own village in the Betawi cultural village, and the already high level of population density in Srengseng Sawah Village which affects the service to the community in Srengseng Sawah Village. Apart from supporting factors, there are also factors that hinder the formation of kelurahan in the Betawi Cultural Village Area, namely another possible consideration in the form of the absence of a village office that will become the center of government.Keywords  :  policy implementation; Betawi Cultural village area; sub-district.